2015
DOI: 10.1016/j.apcata.2015.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Promotion effect of rare-earth elements on the catalytic decomposition of ammonia over Ni/Al2O3 catalyst

Abstract: Please cite this article as: Kaname Okura, Takeou Okanishi, Hiroki Muroyama, Toshiaki Matsui, Koichi Eguchi, Promotion effect of rare-earth elements on the catalytic decomposition of ammonia over Ni/Al2O3 catalyst, Applied Catalysis A, General http://dx. Graphical abstract Graphical abstract Graphical abstract Graphical abstractHighlights Highlights Highlights Highlights • The Ni/Al2O3 catalysts modified by rare-earth elements were investigated.• The addition of rare-earth elements promoted ammonia decompositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
53
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(66 citation statements)
references
References 31 publications
4
53
1
Order By: Relevance
“…Conventionally, supports with a high surface area, such as Ce 0.8 Zr 0.2 O 2 , mesoporous silica, and multiwalled carbon nanotubes (MWCNT), are effective for the high performance of Ni‐based catalytic systems. Moreover, the addition of rare‐earth elements improved the performance of Ni/Al 2 O 3 . These results suggested the suitability of the rare‐earth oxides for the support material of Ni catalysts.…”
Section: Introductionsupporting
confidence: 69%
See 3 more Smart Citations
“…Conventionally, supports with a high surface area, such as Ce 0.8 Zr 0.2 O 2 , mesoporous silica, and multiwalled carbon nanotubes (MWCNT), are effective for the high performance of Ni‐based catalytic systems. Moreover, the addition of rare‐earth elements improved the performance of Ni/Al 2 O 3 . These results suggested the suitability of the rare‐earth oxides for the support material of Ni catalysts.…”
Section: Introductionsupporting
confidence: 69%
“…in which k is a reaction rate constant, and α and γ are reaction orders. Our recent study confirmed that the reaction rate was independent of P normalN2 over Ni catalysts . Thus, it was possible to neglect the effect of P normalN2 on the reaction rate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, Okura et al. investigated Ni‐based catalysts modified by rare‐earth elements and revealed that the rare‐earth elements can promote the ammonia decomposition reaction by alleviating the hydrogen inhibition effect on the catalyst Ni surface. Kishimoto et al.…”
Section: Introductionmentioning
confidence: 99%